2017
DOI: 10.1016/j.sjbs.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Proteins are potent biomarkers to detect colon cancer progression

Abstract: Colon cancer is the most common type of cancer and major cause of death worldwide. The detection of colon cancer is difficult in early stages. However, the secretory proteins have been used as ideal biomarker for the detection of colon cancer progress in cancer patients. Serum/tissue protein expression could help general practitioners to identify colon cancer at earlier stages. By this way, we use the biomarkers to evaluate the anticancer drugs and their response to therapy in cancer models. Recently, the biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 94 publications
(81 reference statements)
1
15
0
Order By: Relevance
“…The prominent Raman peaks of the SW480 cells, compared with the PBMCs, at around 747 cm −1 and 1000-1300 cm −1 regions can be assigned to the molecular structures of the nucleic acids, proteins, and lipids (phospholipids) ( Table 1). The higher intensities of these SERS peaks in SW480 cells demonstrated that there was an increase in the amount of proteins, as expected for cancer cells [49]. Many spectral differences between PBMCs and SW480 cells can be clearly observed, which suggests the feasibility of these substrates to differentiate between different cell populations.…”
Section: Resultssupporting
confidence: 52%
“…The prominent Raman peaks of the SW480 cells, compared with the PBMCs, at around 747 cm −1 and 1000-1300 cm −1 regions can be assigned to the molecular structures of the nucleic acids, proteins, and lipids (phospholipids) ( Table 1). The higher intensities of these SERS peaks in SW480 cells demonstrated that there was an increase in the amount of proteins, as expected for cancer cells [49]. Many spectral differences between PBMCs and SW480 cells can be clearly observed, which suggests the feasibility of these substrates to differentiate between different cell populations.…”
Section: Resultssupporting
confidence: 52%
“…Several techniques have been applied for single-cell studies including microscopic imaging [66,67], patch-clamp [68,69], comet assay [70,71], flow cytometry [72,73], mass spectrometry [74,75], electrophoresis [70,76], fiber optics [77,78] and surface-enhanced Raman spectroscopy (SERS) [15,19,79,80]. Some of the conventional approaches to analyze living cells are based on their surface markers [81,82,83], secreted proteins [84,85,86], metabolites [87,88], phosphoprotein signaling pathway elements [89,90], genomes [91,92] and transcriptome [93,94]. For example, flow cytometry equipped with multiple lasers and detectors can analyze 12 different surface protein markers by multicolor labeling [95].…”
Section: Single-cell Analysis and Surface-enhanced Raman Scatteringmentioning
confidence: 99%
“…It is associated with cytosolic calcium level homeostasis and, inhibition of HSP70 expression, has been shown to stimulate release of intra-cellular calcium in cell culture. Calcium induces cell death by the caspase dependent mechanism in CRC cell lines, and functions in the stabilization of lysosomes and inhibition of apoptosis [84]. Importantly, in other types of cancer such as pancreatic and prostate cancer, HSP70 has been shown to upregulate cell survival [84].…”
Section: Hsp70mentioning
confidence: 99%
“…Calcium induces cell death by the caspase dependent mechanism in CRC cell lines, and functions in the stabilization of lysosomes and inhibition of apoptosis [84]. Importantly, in other types of cancer such as pancreatic and prostate cancer, HSP70 has been shown to upregulate cell survival [84]. In a study of 33 CRC patient plasma samples, using ELISA assays, serum levels of HSP70 were significantly elevated (≥2.25 ng/ml) in cancer patients compared to healthy controls, The sensitivity and specificity of elevated serum HSP70 in the CRC group was reported as 96.77% and 96.96% respectively [85].…”
Section: Hsp70mentioning
confidence: 99%